Redistribution with Performance Pay - Pawel Doligalski; Abdoulaye Ndiaye; Nicolas Werquin (Center for Economic Studies and ifo Institute (CESifo), 2020)
Half of the jobs in the U.S. feature pay-for-performance. We study nonlinear income taxation in a model where such contracts arise in private labor markets that are constrained by moral hazard frictions. We derive novel formulas for the incidence of arbitrarily nonlinear reforms of a given tax code on both the mean of earnings and their sensitivity to performance. We show theoretically and quantitatively that, following an increase in tax progressivity, the higher performance-sensitivity caused by the crowding-out of insurance provided by firms is almost fully offset by a countervailing "performance-pay effect" driven by labor supply responses. As a result, earnings risk is hardly affected by policy. We then turn to the normative analysis of a government that levies taxes and transfers to redistribute income across workers with different levels of uninsurable productivity. We find that setting taxes without accounting for the endogeneity of private insurance is close to optimal. Thus, the common concern that standard models of taxation underestimate the cost of redistribution is, in the context of performance-based compensation, overblown.
Keywords: D61; D82; D86; H21; H22; 330; tax incidence; optimal taxation; moral hazard; performance pay